Synthesis of surface active alkanes for cellulose modification - Moses, Alvira (Stellenbosch : University of Stellenbosch, 2010)
119 leaves single sided printed, preliminary pages and numbered pages 1-101. Includes bibliography and a list of tables, figures, schemes and abbreviations. Digitized at 300 dpi (OCR), used Bizhub 250.